Validation of the nursing history for a Long-Stay Institution for the Elderly - Juliane de Fátima Santos Antunes; Erika Christiane Marocco Duran; Paula Cristina Pereira da Costa; Meiry Fernanda Pinto Okuno (Universidade Federal do Ceará, 2024)
Objective: to construct and validate the content of a nursing history for a Long Stay Institution for the Elderly. Methods: a methodological study divided into the following stages: identification of the main Nursing Diagnoses in the literature, development of the instrument, validation with specialists using the Delphi technique, and restructuring of the instrument based on the Self-Care Deficit Theory. Results: the 41 articles selected resulted in 78 main Nursing Diagnoses, which supported the development of an instrument with 104 items. A total of 37 experts were selected and invited for validation, and 10 agreed to contribute. After validation, the record was finalized with 90 items, with a Content Validation Index between 0.80 and 1.0 in the first round. The suggestions validated in the second round achieved 80-100% agreement to complete the validation of the instrument's content. Conclusion: the content of a nursing history for a Long-Stay Institution for the Elderly based on the Self-Care Deficit Theory was constructed and validated. Contributions to practice: this is an important resource that can be used in clinical practice.